Manajemen kepala sekolah dalam pemberdayaan guru dalam mengelola kelas sekolah dasar - Mulia, Beta Nanda; Marmoah, Sri; Hadiyah, Hadiyah (Universitas Sebelas Maret, 2022)
The Headmaster as a leader in formal education must be visionary. Teachers have a responsibility to see everything going on in the classroom to support the student development process. In the school improvement process, teachers have different assumptions or perceptions about the headmaster's ability to lead. As a mover for teachers, the headmaster must still be able to move teachers so that their performance can improve even in the current pandemic conditions which require headmasters and teachers to also adapt to new habits. This research aims to determine the headmaster's leadership in managing the empowerment of teachers in the classroom management. This research is a kind of descriptive qualitative research to describe something that continues at the time of the study. The results of this research indicate that the management of the headmaster's by empowering teachers to manage the classroom is well implemented.